KEABSAHAN HUKUM TRANSAKSI E – COMMERCE - Dewi Oktoviana Ustien (JSSHA ADPERTISI JOURNAL, 2021)
Trade transactions through the internet are very beneficial for many parties, so that these trade transactions are in great demand, not only for producers but also consumers. Now the Internet has become a special problem since it is used in trade or business activities known as E-Commerce transactions. It is recognized economically, the use of the internet has provided added value in accelerating the transaction process, but juridically, the problem of using the internet is very risky for the parties because its characteristics are very different from conventional business, making it difficult to reach by the applicable legal rules.This research uses a normative juridical approach . And the data used is secondary data which is then analyzed qualitatively. The results of the study indicate that transactions and the validity of agreements on e-commerce are said to be valid if they meet several conditions, namely as stated in Article 1320 of the Civil Code, namely the existence of agreements, skills, exchanged values, and a lawful object. Article 1458 explains about the agreement, which reads "The sale and purchase is considered to have taken place between the two parties, immediately after these people reach an agreement on the object and the price, even though the object has not been delivered, nor has the price been paid". Article 1329 explains about competence: "everyone is capable of making engagements, if he is not declared incompetent by law". Article 1234 explains about the value exchanged: that each engagement is to give something, to do something, or not to do something, and the existence of a lawful object is explained in Article 1333: an agreement must have as a subject an item of at least a specified type, Also Article 1337 of the Civil Code states that what is included in the prohibited causes are those prohibited by law or contrary to decency and public order.